Dirosah Muqoronah Nahwiyah: Al-Khilafu Baina Al-Kholil bin Ahmad wa Sibawaeh Fi Ba'di Masail Nahwiyah - Ismail Ismail (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2017)
Kholil bin Ahmad was born as the Arabs of the tribe al-Azad al-Yamaniyah in the year 100 AH and died in 174. He was nicknamed Mr. Arab Nahwu decent, because he was the first to lay the foundations of qiyas, ta'lil and awamil and develop. Kholil bin Ahmad not compiled a book specifically discusses nahwu, because he did not deign authored a book on disciplines teah compiled others where teachers 'Isa ibn Umar